2022
DOI: 10.1101/2022.02.16.480628
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis for interaction between CLAMP and MSL2 proteins involved in the specific recruitment of the dosage compensation complex in Drosophila

Abstract: Transcriptional regulators select their targets from a large pool of similar genomic sites. The binding of the Drosophila dosage compensation complex (DCC) exclusively to the male X chromosome provides insight into binding site selectivity rules. Previous studies showed that the male-specific organizer of the complex, MSL2, and ubiquitous DNA-binding protein CLAMP directly interact and play an important role in the specificity of X chromosome binding. Here we studied the highly specific interaction between the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…We recently found that the region of 1–153 amino acid residues can homodimerize in the Y2H assay [ 46 ]. For detailed mapping of the CLAMP domain involved in homodimerization, we tested different variants of the N-terminal region for interaction in the Y2H assay.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently found that the region of 1–153 amino acid residues can homodimerize in the Y2H assay [ 46 ]. For detailed mapping of the CLAMP domain involved in homodimerization, we tested different variants of the N-terminal region for interaction in the Y2H assay.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the folding state of the CLAMP N-terminal domain, we used NMR spectroscopy. We measured the 15 N-HSQC NMR spectrum of 15 N-labeled CLAMP 1–113 and compared it with a spectrum of CLAMP 87–153 including the zinc-finger region for which the resonance assignments were obtained previously ([ 46 ], BioMagResBank ID: 34600 Available online: (accessed on 26 December 2021). All H N chemical shifts of the 1–86 region are plotted into the interval from 7.6 to 8.6 ppm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…198 199 MSL2 is the structural component of MSLc and is usually found complexed with other members (Hallacli et al 2012). However, MSL2 has some affinity for DNA sequence in both D. melanogaster and D. virilis (Villa et al 2016(Villa et al , 2021 and CLAMP and MSL2 directly interact with each other through well-conserved domains (Tikhonova et al 2022b), suggesting that CLAMP might recruit MSL2 outside of the complex. We therefore stained chromosome spreads for another MSLc member, MSL3.…”
Section: A D Melanogaster Female Dapi Mxc Clampmentioning
confidence: 99%